BEST PRACTICE PENGEMBANGAN KURIKULUM MELALUI PROGRAM “SI BIAS” DI SEKOLAH DASAR KATOLIK DIAKONIA - Iis Indirianti; Dhiniaty Gularso (STKIP Subang, 2026)
This study aim to describe curriculum development through the SI BIAS Program (Spirituality, Integrity, Compassion, Inclusiveness, Activeness, and Solidarity) as an effort to strengthen character education at SD Katolik Diakonia. The study employed a descriptive qualitative method with a best practice approach. Data were collected through observation, documentation, and program reflection and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that the SI BIAS Program was successfully integrated into intracurricular, co-curricular, extracurricular activities, and school culture. The program was implemented through daily habituation, integration of character values into learning activities, social programs, and role modeling by all school members. The program positively influenced students’ discipline, responsibility, honesty, social awareness, cooperation, and spirituality. The study concludes that school culture-based curriculum development implemented in an integrated manner can create a positive learning environment and effectively strengthen students’ character.